PENGGUNAAN KONJUNGSI SEBAGAI UNSUR KOHESI PADA BERITA UTAMA SURAT KABAR HARIAN SINGGALANG EDISI MEI—JUNI 2020 - Aurora, Novia; Atmazaki, Atmazaki (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this study is to describe the use of conjunction on utama news of Harian Singgalang edition Mei—Juni 2020. This type of research is qualitative research using descriptive methods. The data in this study were obtained from the results of a documentation study with the observation and note technique. The techniques used to analyze data are data identification, data presentation, and drawing conclusions. The research results found 978 times the use of conjunctions in 45 data sources with 638 sentences. Coordinative conjunctions were found 518 times, subordinative conjunctions were found 336 times, correlative conjunctions were found 14 times, conjunctions between sentences were found 102 times, and conjunctions between paragraphs was found 8 times. Based on the results of the study, it is concluded that the most common conjunctions found are coordinative conjunctions while the least conjunctions found are conjunctions between paragraphs. Besides, the use of correct conjunctions outweighs the use of improper conjunctions. Kata Kunci: Konjungsi, Kohesi, Berita Utama